Experimental study on three-effect tubular solar still under vacuum and immersion cooling - Yan, Tiantong; Xie, Guo; Chen, Wenlong; Wu, Zhanglin; Xu, Jialing; Liu, Yingzhang (Elsevier, 2021)
Solar still is widely used for supplying fresh water to small communities in remote areas. One drawback of this technique lies in the low freshwater yield. Recent studies on stills of multi-effect and vacuum design proved their potential for high yield. However, such systems suffer from high electricity consumption and insufficient cooling. In this study, a novel system with a periodic pressure control scheme and water immersion cooling has been proposed to mitigate these defects. A prototype was constructed and associated with a 0.19-m2 solar panel. A 5-day outdoor experiment was conducted to evaluate the overall performance. Results indicated that the highest yield during the test was 9.8 kg/m2 at operating pressure of 40 kPa. A significant performance ratio of 1.87 was achieved with immersion cooling, i.e., 0.42 higher than that with air cooling. Thermal analysis showed that the heat transfer coefficient of water immersion cooling was 15–50 times higher than that of air cooling. Compared with previous vacuum-operated systems, the specific electricity consumption of maintaining vacuum was greatly reduced, i.e., from 21.6 kJ/kg to 1.7 kJ/kg for the case at 60 kPa. The forecast cost of the distilled water is $0.012/kg, representing an affordable desalination technique for off-grid communities.
Keywords: Electricity consumption; Tubular; Immersion cooling; Vacuum; Solar still